A SCOPING REVIEW: PROFESSIONALISM ACCOUNTING EDUCATORS IN THE POSTDIGITAL ERA - Rohmatin, Yunia; Eka Ananta Sidharta; Nurika Restuningdiah (Brilliant International Journal Of Management And Tourism, 2022)
Teacher professionalism during a pandemic is an interesting topic because there are no clearly defined sections on what professionalism looks like during a pandemic and what teachers should do today that appear across stakeholder groups (Hollweck, 2020). This study aims to find out how the professionalism of accounting educators is during the co-19 pandemic in all countries affected by the co-19 pandemic. The research method uses a “scoping review” from Arksey and O'Malley (2005). The Scope of Research reviews relevant international journals with related research titles and focuses. The research was conducted spanning 2019-2022 and journals were taken from ten databases with official websites registered or subscribed to by the Malang State University Library and the National Library of the Republic of Indonesia. The results of the research conducted in the 2019-2022 timeframe show that 12 journal articles match the research questions. Most of the research publication years are in 2020. The results of the research show that the professionalism of accounting educators in the post-digital era can be seen in the online learning and assessment process (Amit Joshi and Muddu Vinay, 2020). The gap in practice in accounting education makes universities and professional institutions in the future expected to work together in developing accounting curricula